PENGARUH KINDERFLIX TERHADAP KEMAMPUAN MELONCAT ANAK USIA DINI - Maria Qori’ah; Farah Devi Husain; Vina Rohmatul Ummah; Viena Wanidha Andriani (FORPIM PTKIS ZONA TAPAL KUDA, 2026)
The current technological era makes Kinderflix-based audio-visual media the latest breakthrough in stimulating children's gross motor skills to jump correctly according to foot support. This study aims to determine the effect of Kinderflix-based audio-visual media on the jumping ability of children aged 4-5 years through animal themes at RA Al Anwar, Balak Village, Songgon District. The implementation of this study uses a quantitative method with the type of Pre-Experimental Design. The population in this study has 12 children aged 4-5 years with purposive sampling to 8 children according to problems in children's abilities. Non-participant observation was carried out as data collection using observation sheets, as well as documentation of the implementation of the study. The results of data collection were analyzed using statistical tests with prerequisite tests first using normality tests with a pretest significance value of 0.246 and a posttest significance value of 0.334 which were normally distributed. The results of the hypothesis test using the t-test (Paired Dependent Sample T Test) with the help of the IMB SPSS statistics 26 application, where the sig. (2-tailed) value shows a significance value of 0.026 <0.05 that kinderflix-based audio-visual media has an effect on the jumping ability of children aged 4-5 years. The research findings show that children's jumping ability can be stimulated through movements imitating surrounding animals. This research is expected to provide theoretical and practical contributions in stimulating the jumping ability of early childhood as a foundation for realizing the next golden generation.